LEGAL CERTAINTY REGARDING THE TIME LIMIT FOR CLAIMING RETIRED EMPLOYEES RIGHTS IN INDONESIA - Sholikah, Umi Nuris; Ardila, Winda; Rizkiyah, Salma Putri; Muangsong, Natcha (Universitas Negeri Surabaya, 2024)
Retirement marks the end of the employment relationship between an employee and the company, in which the employee is entitled to resignation, work time remuneration, and compensation rights. However, in the prosecution of his charges there are still obstacles such as the complexity of administrative procedures to the issue of the provisions of due date. Deadline is a form of time limit that has been established for filing a claim, which, when the time limit is passed, a person's right to fil a claim is deemed to be expired. Rules concerning delay are governed by a number of legislative regulations, including UNCITRAL and employment laws. Nevertheless, these provisions are often not well understood by employees, especially those who work in small companies or the informal sector. Late filing of claims for employee rights is often due to a lack of socialization and education about the employee's own rights. That affects the decline in the well-being of retired employees. Legal certainty is needed to help fulfil the rights of both working and retired employees.